Tendencies - Sedgwick, Eve Kosofsky 1950-2009 (Series Q, 1993)
Tendencies brings together for the first time the essays that have made Eve Kosofsky Sedgwick "the soft-spoken queen of gay studies" (Rolling Stone). Combining poetry, wit, polemic, and dazzling scholarship with memorial and autobiography, these essays have set new standards of passion and truthfulness for current theoretical writing.The essays range from Diderot, Oscar Wilde, and Henry James to queer kids and twelve-step programs; from "Jane Austen and the Masturbating Girl" to a performance piece on Divine written with Michael Moon; from political correctness and the poetics of spanking to the experience of breast cancer in a world ravaged and reshaped by AIDS. What unites Tendencies is a vision of a new queer politics and thought that, however demanding and dangerous, can also be intent, inclusive, writerly, physical, and sometimes giddily fun